ERP ODOO in the sale process of an PYME in the Gastronomy Sector (LACCEI, 2024)
The following article corresponds to the implementation of the ERP ODOO in the sale process of Chifa Wang S.A.C. from the city of Trujillo, Peru. For this, a Pre-Experimental research approach is followed, where information gathering techniques such as survey and observation are used. For the implementation, the methodology proposed by VAUXOO Open source Specialist was developed, in which it specifies the following stages: Stage 1: Gap analysis, Stage 2: Supplier analysis, Stage 3: Concept and functionalities tests, Stage 4: Import of data, Stage 5: Validation and training, Stage 6: Go Live deployment, Stage 7: Second use in which it was concluded that the development contributed to increase the quality of the sales process, which is evidenced in an improvement of 16.75% of the completion time, productivity by 16.79% of the maximum capacity of order attention per working day, a 56.52% reduction in errors made during sales and the increase in the level of customer satisfaction in relation to the process by 30.39%. The research is described in introduction, state of the art, objectives, material and methods, methodology for the implementation of ERP ODOO, results, discussions and conclusions.